1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 173 (1809) - (:unkn) unknown (My University, 1632)
"NOE man shall goe or send abroade without a sufficient party well armed." And "NOE man shall goe to worke in the grounds without theire armes, and a centinell uppon them" And "ALL men that are fittinge to beare armes, shall bringe their pieces to the church"
Keywords: REQUIRED POSSESSION; TRAVEL; CARRY - CERTAIN PUBLIC PLACES; SENSITIVE PLACES